Structure-based design and biological characterization of selective histone deacetylase 8 (HDAC8) inhibitors with anti-neuroblastoma activity - Heimburg, Tino; Witt, Olaf (Journal of medicinal chemistry, 2017)
Histone deacetylases (HDACs) are important modulators of epigenetic gene regulation and additionally control the activity of non-histone protein substrates. While for HDACs 1-3 and 6 many potent selective inhibitors have been obtained, for other subtypes much less is known on selective inhibitors and the consequences of their inhibition. The present report describes the development of substituted benzhydroxamic acids as potent and selective HDAC8 inhibitors. Docking studies using available crystal structures have been used for structure-based optimization of this series of compounds. Within this study, we have investigated the role of HDAC8 in the proliferation of cancer cells and optimized hits for potency and selectivity, both in vitro and in cell culture. The combination of structure-based design, synthesis, and in vitro screening to cellular testing resulted in potent and selective HDAC8 inhibitors that showed anti-neuroblastoma activity in cellular testing.